2011
DOI: 10.1111/j.1539-6924.2011.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Validation of Statistical Methods for Predicting Power Outage Durations in the Event of Hurricanes

Abstract: This article compares statistical methods for modeling power outage durations during hurricanes and examines the predictive accuracy of these methods. Being able to make accurate predictions of power outage durations is valuable because the information can be used by utility companies to plan their restoration efforts more efficiently. This information can also help inform customers and public agencies of the expected outage times, enabling better collective response planning, and coordination of restoration e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 164 publications
(101 citation statements)
references
References 15 publications
(17 reference statements)
0
96
0
Order By: Relevance
“…Supervised learning theory is a branch of statistical learning methods that has been extensively applied to areas ranging from risk and resilience analysis to hydrological modeling 710 . Supervised learning models vary widely in their degree of complexity, stability, flexibility and interpretability, and can be categorized as parametric, semi-parametric or non-parametric methods.…”
Section: Resultsmentioning
confidence: 99%
“…Supervised learning theory is a branch of statistical learning methods that has been extensively applied to areas ranging from risk and resilience analysis to hydrological modeling 710 . Supervised learning models vary widely in their degree of complexity, stability, flexibility and interpretability, and can be categorized as parametric, semi-parametric or non-parametric methods.…”
Section: Resultsmentioning
confidence: 99%
“…The time to repair for each damaged component is stochastic in its nature. In [27], it was shown that the repair time is not only a function of the number of crews, but also other factors, e.g., geographical characteristics of the area that limit crews access can affect the repair time. On the other hand, because of the variation in skill level of the repair crew along with the random nature of the degree of damage, the time to repair need to be considered as a random variable.…”
Section: A Module 1: Component Outagesmentioning
confidence: 99%
“…However, the availability of past data could be a challenging issue which limits the model practicality. Reference [27] compared the regression methods and data mining techniques for predicting power outage durations during hurricanes. The accuracy of Bayesian additive regression trees (BART) outperformed the other models in their study.…”
Section: ) Outage Predictionmentioning
confidence: 99%
“…While Nateghi et al [49] and Guikema et al [29] follow a similar approach, both estimating Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/ijdrr outages as a function of climatic, topographical, land cover, human and material resources, and population densities amongst others. Ultimately these approaches require a significant amount of potentially difficult to obtain input data which can be limited in accuracy -if accessible at all.…”
Section: Introductionmentioning
confidence: 97%